Les experts français de la Haute commission alliée (1949-1955) : un positionnement singulier, entre spécialistes et diplomates ? - Silvère Gaudin (Tr@jectoires)
Between 1949 and 1955, the Federal Republic of Germany was supervised by the Allied High commission, which comprised American, British, and French members. The French control policy relied on economic, juridical and military specialists to be influent in the complex international context marked by the Cold War and the European construction. These experts, less known than political or cultural actors, played a key role in the civil occupation. Based on French diplomatic archives, this article aims to prove that the singular position of these experts, between technicians and diplomats, influenced simultaneously the French policy in Germany and their careers.